The Farmers' Perceptions of Processed Morage Leaf Pudding in Padang Village (Case study in Padang Village, Manggeng District, Aceh Barat Daya Regency) - Maulidin Maulidin; Dedy Darmansyah (Britain International for Academic Research (BIAR-Publisher), 2021)
Moringa is a plant which has a myriad of benefits, Moringa leaves which have complete nutritional content are very good for daily consumption to meet protein for the body, especially children in their infancy. This research was conducted in the village of Padang, Manggeng District, Southwest Aceh Regency, the purpose of this study was to find out how farmers' perceptions of processed Moringa leaf pudding in the village of Padang. From the research results, it is known that farmers' perceptions of processed Moringa leaves can be categorized as good, from the highest total value of the overall research results obtained a perception value of 92.67%, and the lowest value of 82.67%, this value indicates that farmers' perceptions of processed leaves Moringa is good and can be used for food to meet daily nutritional needs. The conclusion drawn in this study is that Moringa is a plant that contains a lot of nutrients that is easy to process as food and has an attractive color and good taste.